Risk control, rights and legitimacy in the limited liability State - Pratt, John (The British journal of criminology, 2017)
Although controlling risk has become a prevalent theme in contemporary penal development in the main English-speaking societies, the range and extent of these measures is limited and specific, indicative of new obligations and reciprocities between state and citizen following post-1980s restructuring. Individuals are exhorted to take care of themselves, but the state remains committed to managing risks thought beyond their control and likely to cause irreparable harm through innovative penal measures. The paper explains how these have coalesced around risks to community cohesion and sexual attacks on women and children; and how these measures have then been legitimated, given that they contravene previous long-standing rules, principles and conventions intended to prohibit or restrict their use.